Mitochondrial regulation in human pluripotent stem cells during reprogramming and β cell differentiation - Jasra, Ila Tewari; Cuesta-Gomez, Nerea; Verhoeff, Kevin; Marfil-Garza, Braulio A.; Dadheech, Nidheesh; Shapiro, A. M. James (Frontiers in Endocrinology, 2023)
Mitochondria are the powerhouse of the cell and dynamically control fundamental biological processes including cell reprogramming, pluripotency, and lineage specification. Although remarkable progress in induced pluripotent stem cell (iPSC)-derived cell therapies has been made, very little is known about the role of mitochondria and the mechanisms involved in somatic cell reprogramming into iPSC and directed reprogramming of iPSCs in terminally differentiated cells. Reprogramming requires changes in cellular characteristics, genomic and epigenetic regulation, as well as major mitochondrial metabolic changes to sustain iPSC self-renewal, pluripotency, and proliferation. Differentiation of autologous iPSC into terminally differentiated β-like cells requires further metabolic adaptation. Many studies have characterized these alterations in signalling pathways required for the generation and differentiation of iPSC; however, very little is known regarding the metabolic shifts that govern pluripotency transition to tissue-specific lineage differentiation. Understanding such metabolic transitions and how to modulate them is essential for the optimization of differentiation processes to ensure safe iPSC-derived cell therapies. In this review, we summarize the current understanding of mitochondrial metabolism during somatic cell reprogramming to iPSCs and the metabolic shift that occurs during directed differentiation into pancreatic β-like cells.